Oncolytic Adenovirus Coding for a Variant Interleukin 2 (vIL-2) Cytokine Re-Programs the Tumor Microenvironment and Confers Enhanced Tumor Control - Quixabeira, Dafne C. A.; Zafar, Sadia; Santos, Joao M.; Cervera-Carrascon, Victor; Havunen, Riikka; Kudling, Tatiana V.; Basnet, Saru; Anttila, Marjukka; Kanerva, Anna; Hemminki, Akseli (Frontiers in Immunology, 2021)
The notion of developing variants of the classic interleukin 2 (IL-2) cytokine has emerged from the limitations observed with the systemic use of human IL-2 in the clinic: severe adverse events accompanied by low therapeutic response rate in treated patients. Modifications made in the IL-2 receptor-binding structure leads to preferential expansion of effector anti-tumor lymphocytes over T regulatory (TReg) cells. Because of their inherent immunogenicity, oncolytic adenoviruses are useful for expression of immunomodulatory molecules in tumors, for induction of a pro-inflammatory state in the tumor microenvironment. In the present study, we constructed an adenovirus coding for an IL-2 variant (vIL-2) protein, Ad5/3-E2F-d24-vIL2. Functionality of the new virus was tested in vitro, and anti-tumor efficacy and mechanism of action studies were performed in immunocompetent hamsters bearing pancreatic tumors. Ad5/3-E2F-d24-vIL2 treatment elicited efficient anti-tumor response, with 62.5% monotherapy complete response. Moreover, it promoted substantial repression of genes associated with myeloid cells mediated immunosuppression (CD11b, ARG1, CD206). This was seen in conjunction with marked improvement of tumor-infiltrating lymphocyte (TILs) cytotoxicity, through the upregulation of CD3G, SAP, PRF1, GZMM and GZMK. In summary, Ad5/3-E2F-d24-vIL2 demonstrates therapeutic potential by counteracting immunosuppression and in efficiently coordinating lymphocytes mediated anti-tumor response in immunosuppressive tumors. Thus, Ad5/3-E2F-d24-vIL2 is a promising candidate for translation into clinical trials in human immunosuppressive solid tumors.